Patterns and Trends of SSCS Model Implementation in Science Literacy Development: Systematic Literature Review 2015-2024 - Laksmi Fidya Arini; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
This study analyzes the patterns and trends of the implementation of the Search, Solve, Create, and Share (SSCS) learning model in the development of scientific literacy through a systematic literature review in the period 2015-2024. Scientific literacy is a crucial component in 21st century education that includes not only mastering scientific concepts, but also developing the skills to apply knowledge in real life. Indonesia's low ranking in the 2022 PISA assessment (ranked 77th out of 81 countries with a score of 394) indicates the need for Learning Innovation, one of which is through the SSCS model. Using the Systematic Literature Review method, the study analyzed 40 articles from 450 identified publications. The results showed a significant increase trend in SSCs-related publications since 2019 with a cumulative annual growth of 33.2%. The research was dominated by quantitative methods (65%), followed by mixed methods (25%), and qualitative (10%). The implementation of SSCS is proven to be effective in improving various skills, including critical thinking, problem solving, creativity, and understanding concepts at various levels of Education. The implementation of the SSCS model is also successfully integrated with other approaches such as interactive multimedia, ethnoscience, TPACK, and local wisdom values. These findings imply that the SSCS model is a potential learning strategy to improve science literacy and support 21st century skills development in Indonesia.